THE INFLUENCE OF TRAINING AND DISCIPLINE ON EMPLOYEE PERFORMANCE IN PT Y-TECH AUTOPARTS INDONESIA - Setiawan, Indra (Journal of Business, Management, and Accounting, 2020)
The development of the automotive industry is increasingly rapid and makes competition in the industry more stringent between one industry with another industry. This research aims to examine the effect of Training and Discipline on Company Performance. This study uses simple random sampling, because because all members are given the same opportunity to become a sample, the sample of this study amounted to 58 respondents of PT Y-Tech Autoparts Indonesia employees. The testing method uses the processing of IBM SPSS Version 22 Analysis to test the effect of Training and Discipline on Company Performance. The results of the study indicate that Training and Discipline have a positive effect on employee performance and the Discipline variable has a large influence on performance.